Disrupted-in-schizophrenia 1 Protein Misassembly Impairs Cognitive Flexibility and Social Behaviors in a Transgenic Rat Model. (15th June 2022) - Wang, An-Li; Chao, Owen Y.; Nikolaus, Susanne; Lamounier-Zepter, Valeria; Hollenberg, Cornelis P.; Lubec, Gert; Trossbach, Svenja V.; Korth, Carsten; Huston, Joseph P.
Graphical abstract: Highlights: In water maze tasks, tgDISC1 rats were deficient in flexible adaptation. tgDISc1 rats displayed less social interaction. DISC1 gene overexpression impairs cognitive flexibility and social behaviors. Abstract: Alterations in cognitive functions, social behaviors and stress reactions are commonly diagnosed in chronic mental illnesses (CMI). Animal models expressing mutant genes associated to CMI represent either rare mutations or those contributing only minimally to genetic risk. Non-genetic causes of CMI can be modeled by disturbing downstream signaling pathways, for example by inducing protein misassembly or aggregation. The Disrupted-in-Schizophrenia 1 ( DISC1 ) gene was identified to be disrupted and thereby haploinsufficient in a large pedigree where it was associated with CMI. In a subset of CMI patients, the DISC1 protein misassembles to an insoluble protein. This has been modeled in a rat (tgDISC1 rat) where the full-length, non mutant human transgene was overexpressed and cognitive impairments were observed. Here, we investigated the scope of effects of DISC1 protein misassembly by investigating spatial memory, social behavior and stress resilience. In water maze tasks, the tgDISC1 rats showed intact spatial learning and memory, but were deficient in flexible adaptation to spatial reversal learning compared to littermate controls. They also displayed less social interaction. Additionally, there was a trend towards increased corticosterone levels after restraint stress in the tgDISC1 rats. Our findings suggest that DISC1 protein misassembly leads to disturbances of cognitive flexibility and social behaviors, and might also be involved in stress sensitization. Since the observed behavioral features resemble symptoms of CMI, the tgDISC1 rat may be a valuable model for the investigation of cognitive, social and – possibly – also stress-related symptoms of major mental illnesses.